Respuesta :
Answer:
[tex] \bf{= \frac{64 {x}^{3} - 1 }{4x - 1} }\\ \\ \bf{= \frac{( \cancel{4x - 1})(16 {x}^{2} + 4x + 1) }{ \cancel{4x - 1}}} \\\\ \bf{= 16 {x}^{2} + 4x + 1}[/tex]
Answer:
[tex]16x^2+4x+1[/tex]
Step-by-step explanation:
Given expression:
[tex]\dfrac{64x^3-1}{4x-1}[/tex]
Step 1
Factor the numerator of the given expression.
Rewrite 64 as 4³ and 1 as 1³:
[tex]\implies (4^3)x^3-1^3[/tex]
[tex]\textsf{Apply the exponent rule} \quad a^b \cdot c^b=(ac)^b:[/tex]
[tex]\implies (4x)^3-1^3[/tex]
[tex]\textsf{Apply the Difference of Cubes Formula} \quad x^3-y^3=\left(x-y\right)\left(x^2+xy+y^2\right):[/tex]
[tex]\implies (4x)^3-1^3=(4x-1)\left((4x)^2+4x(1)+(1)^2\right)[/tex]
[tex]\implies (4x)^3-1^3=(4x-1)\left(16x^2+4x+1\right)[/tex]
Step 2
Replace the numerator in the given expression with the factored numerator from step 1:
[tex]\implies \dfrac{64x^3-1}{4x-1}=\dfrac{(4x-1)\left(16x^2+4x+1\right)}{4x-1}[/tex]
Cancel the common factor (4x - 1):
[tex]\implies 16x^2+4x+1[/tex]